What Is the Best Available Evidence for Using Homeopathy in Patients with Intellectual Disabilities? - Shaddel, Farshad (Iran J Pediatr, 2014)
Objective: The debate about the effectiveness of homeopathy hits the headlines from time to time. Reported evidences for the role of homeopathy in psychiatric illness relevant to people with intellectual disabilities are patchy and inconsistent. In this review we summarize the best available evidence for the use of homeopathy to treat the psychiatric disorders common in this population. Methods: Systematic literature review was conducted through February 2012 to July 2012 in AMED, CINHAL, BNI, EMBASE, MEDLINE, PSYCHINFO and GOOGLE SCHOLAR. In the next steps thirty eight homeopathic associations were contacted and a top-up literature search was done on Scopus and World of Science databases till March 2014. Twelve relevant clinical trials were identified and included in this study. The quality of each trial was assessed by the Oxford quality scoring system (Known as Jadad score) as well as subjective review by two reviewers independently (good versus poor). Findings : The largest body of evidence pertained to the use of homeopathy in the treatment of attention deficit hyperactivity disorder (ADHD). There is heterogeneity in the quality of trials and also the outcome of studies but overall our findings suggest some potential for using homeopathy in ADHD. Current evidences do not support the use of homeopathy for treatment of speech and language difficulties. There was only one trial concerning the use of homeopathy in Autistic Spectrum Disorder. This was of a poor quality and unable to provide any recommendation. Conclusion: Whilst acknowledging the risk of publication and language bias in our study, the currently available evidences are neither conclusive nor comprehensive enough to give us a clear picture for the use of homeopathy in patients with intellectual disabilities. There are large gaps in the body of evidence concerning the role of homeopathy in the treatment of common disorders in intellectual disability, such as autism, challenging behavior or developmental arrest in childhood.